2021
DOI: 10.1029/2021ea001711
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cylindrical THF Hydrate Veins on the Undrained Behavior of Fine‐Grained Soils

Abstract: The last few decades have seen considerable interest in methane gas hydrates, an ice-like compound comprised of methane gas and water that forms in deep-water marine sediments on continental margins and below permafrost in Arctic regions (Kvenvolden & Lorenson, 2001), as a future energy resource (Boswell & Collett, 2011). This is especially true for coarse-grained sediments where the high intrinsic permeability and high hydrate saturations, up to 90% of available pore space (e.g., Boswell et al., 2016), make t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 75 publications
(92 reference statements)
0
3
0
Order By: Relevance
“…The degree of consolidation U is an important parameter used to measure the degree of underconsolidation of sediments. , To fully study the impact of the degree of consolidation U on the mechanical characteristics of MHBSs, Figures and respectively illustrate the curve of the Secant Young’s modulus E 50 and failure strength q f relationship between the degree of consolidation U . In order to compare the validity of data, experimental data of others ,,,, are introduced in figures. The E 50 is typically determined by considering the slop of a line that joins the origin to the point (where is the point at half of failure strength q f ) on the stress–strain curve, which helps to reduce the issues associated with seating–bedding errors. , The deviator stress corresponding to 15% strain is the value of failure strength .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The degree of consolidation U is an important parameter used to measure the degree of underconsolidation of sediments. , To fully study the impact of the degree of consolidation U on the mechanical characteristics of MHBSs, Figures and respectively illustrate the curve of the Secant Young’s modulus E 50 and failure strength q f relationship between the degree of consolidation U . In order to compare the validity of data, experimental data of others ,,,, are introduced in figures. The E 50 is typically determined by considering the slop of a line that joins the origin to the point (where is the point at half of failure strength q f ) on the stress–strain curve, which helps to reduce the issues associated with seating–bedding errors. , The deviator stress corresponding to 15% strain is the value of failure strength .…”
Section: Discussionmentioning
confidence: 99%
“…Iwai et al 31 carried out an undrained shear test on sandy MHBSs containing carbon dioxide, and they observed the negative pore pressure during shearing. Priest et al 32 studied the effect of THF hydrate veins on the undrained characteristics of fine-grained soils sediments; they found that the increase of vein diameter and confining pressure would increase the stiffness and strength of sediments and the excess pore water presented positive pressure. Wang et al 18 completed consolidated-undrained (CU) triaxial tests on gas hydrate-bearing clayed sediments, and the consequence of the tests showed that the failure strength and cohesion increased with the increase of the initial effective stress and hydrate saturation.…”
Section: Introductionmentioning
confidence: 99%
“…There have been a large number of studies on the mechanical properties of HBS at the macro-scale, and the main influencing factors have been found, such as hydrate saturation, , effective confining pressure, temperature, , overconsolidated ratio (OCR), occurrence conditions (mainly pore fluid), , hydrate shape, content of fine composition, and so on. Nevertheless, the research of the mechanical characteristics of HBS over time is equally important, which is an important evaluation criterion for forecasting the long-term stability of the deformation behavior of hydrate reservoirs.…”
Section: Introductionmentioning
confidence: 99%